Prediction Power of Diploma Value Against Academic Achievement of Students on Health Polytechnic of Semarang - Warijan; Wahyudi, Teguh; Abidin, M. Zainal; Titah, Ajeng (Advances in Social Sciences Research Journal, 2021)
In the field of education, there is a routine that occurs every new academic year, in which each university has a new student admission process with a different recruitment system. The Poltekkes of the Ministry of Health in Semarang conducted a screening of students from the Interest and Achievement Tracking (PMDP), Sipenmaru and Independent Pathways. In this recruitment system, a certificate, although it is used as a mandatory administrative requirement when registering, has not been fully utilized in an effort to predict student academic achievement. Actually, the value on a diploma can provide a more complete picture of a person’s academic ability, because it is a reflection of the learning process that is followed during school because it is a combination of the average grades of grades 1, 2 and 3, school exam scores and national exam scores. The research objective was to analyze the effect of the average value of a diploma on the cumulative academic achievement index (GPA) of semester I-IV students at the Poltekkes Kemenkes Semarang. This type of research isresearch correlational and regressioninvolving respondents from Diploma 3 (D3) and Diploma 4 (D4) students in odd and even semesters of the 2019/2020 Academic Year at the Poltekkes of the Ministry of Health in Semarang, batch 2019, 2018, 2017, and 2016. The data were collected using observation sheets and the collected data were processed using usingcorrelation analysis pearson product moment and linear regression to determine the relationship and influence of independent variables with the dependent variable. Results There is a significant influence on the average value of a diploma on the cumulative grade point average (GPA) of D3 and D4 students of the Health Polytechnic of the Ministry of Health Semarang in 2016, 2017, 2018, and 2019. It is proven that the results of the calculation of rxy are greater than the r table both at the level of significant 5% and a significant level of 1%, with r count of 0.315 while r table of 0.20 and 0.40. and has a determination coefficient of 0.099. The effective contribution given by the variable the average value of the diploma to the cumulative grade point average (GPA) of D3 and D4 students in 2016, 2017, 2018, and 2019 was 9.9%. and 90.1% is influenced by other variables not examined. Suggestions for admission of Polkesmar students should consider taking from high school graduates with good average diploma scores. In addition to increasing the accreditation value of each D3 and D4 Study Program, as well as improving infrastructure both software and hardware, while still increasing the human resources of education practitioners, as well as all parties responsible for the implementation of education.